Aeromagnetic survey over an active stratovolcano in central Mexico (2002)
In this paper, we briefly summarize an aeromagnetic survey over a large stratovolcano (Popocatepetl) and surrounding volcanic terrain in central Mexico to show the potential that recent improvements in these methods have in studying active volcanoes.